Integralis-Moderat: Potret Politik Mohammad Natsir - Nursahid, Fajar; Fata, Ahmad Khoirul (KALAM, 2020)
Some scholars conclude that someone who believes in the unity of religion-state tends to have resistance to modern Western political ideas and institutions. This view is rooted in the history of the emergence of modern political concepts and institutions which are the antithesis of medieval European political institutions, namely theocracy. As opposed to the absolutism of the Church of the Middle Ages, modern political ideas make all that is colored religious-political integration into a negative. This blurry picture has also hit the Islamic world to this day. By using a historical approach, this paper raises the political ideas and actions of the General Chairman of the Masyumi Party, Mohammad Natsir. He is a prominent Islamic political figure who carries the idea of state-religion integration. This article focuses on discussing the construct of Natsir's religion-state integration paradigm, and Natsir's political attitude towards Western political concepts. This article finds that Natsir does believe in the necessity of unifying religion with politics, however, he can accept modern Western political ideas and institutions. More than that, Natsir actually rejected absolute political institutions such as theocracy or monarchy. Thus, it can be concluded that the proponents of the idea of state-religion integration are not always anti-modern ideas (such as democracy) or support an absolute political system such as theocracy. Natsir became clear evidence of an integralist as well as moderate.